Pengembangan Sistem Penyewaan Kendaraan Kota Malang Berbasis Android menggunakan Metode Pengembangan MASAM (Mobile Application Software Agile Methodology) - Meita Putri Aidha; Adam Hendra Brata; Komang Candra Brata (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Vehicle usage in Indonesia is increasingly, because the function of vehicle is very helpful for indonesian people. This is indicated by 111 million Indonesians already using vehicles. Penetration of vehicle rental services in Indonesia is predicted to increase with prediction 1.7% in 2017 and 2.3% in 2021. From survey collected by writer to 31 respondents, 96,8% of respondents need vehicle rental system in Malang City to facilitate them to search available vehicle and rent vehicle. Because to find available vehicle and rent vehicle, they still use telephone, SMS and social media. In this study the authors build a vehicle rental system. The platform used to develop this system is android, because 76.46% of Indonesian people use android. To develop the system, author decided to use MASAM as a development method which is one of the derivatives of the agile development method. The MASAM method supports rapid development and avoids complex development methods by utilizing the domain knowledge and UI Prototyping to find out the user desires. The results of usability testing obtained by using SUS method is 79.4 from customer and 72.5 from rental. So it can be concluded this system is acceptable and easy to use by the user.